ANALISIS KENDALI OTOMATIS PENYEMPROTAN PESTISIDA PADA LAHAN PERTANIAN DENGAN MENGGUNAKAN UAV (UNMANNED AERIAL VEHICLE) - Farid Rahman Wicaksono (2020)
Indonesia is an agrarian country, but the level of productivity is not comparable with the existing workforce, one of the causes is the ineffectiveness of spraying pesticides on agricultural land, that is the background of the creation of agricultural UAV, current UAV are already good but are felt to still have a few shortcomings, namely still controlled by humans which can cause human error effects, using the autopilot system is thought to cut the effect of human error so that spraying is more perfect. The first step in this research is to design and design a UAV for pesticide extraction, how to obtain the required parameters, make a Simulink block diagram, determine the appropriate PID to get a motion or roll scheme that is either roll or pitch. The results of this study found that the time required to go roll as far as 100m with a slope of 30◦ is 8.42 seconds, while to pitch as far as 4m with an angle of 30◦ takes 3.63 seconds.